Frostfire - Hocking, Amanda (New York : St. Martin's Griffin, 2015)
Tracker Bryn Aven's goal of becoming a member of the elite King's Guard is threatened when she is sent to stop Konstantin, a fallen hero who she once secretly loved, who appears to be kidnapping changelings.
Keywords: Young adult fiction; Fantasy fiction